A case for realigning species limits in the southern Australian whipbirds long recognised as the Western Whipbird (Psophodes nigrogularis). (3rd July 2017) - Burbidge, Allan H.; Joseph, Leo; Toon, Alicia; White, Lauren C.; McGuire, Angela; Austin, Jeremy J.
ABSTRACT: The Western Whipbird ( Psophodes nigrogularis ) has a highly disjunct west–east distribution across southern Australia. Earlier morphological analyses recognised four subspecies in one species: P. n. nigrogularis and P. n. oberon in south-west Western Australia, and P. n. leucogaster of the Eyre and Yorke Peninsulas and the Murray Mallee, and P. n. lashmari, restricted to Kangaroo Island, both in eastern Australia. Later morphological analyses elevated P. n. nigrogularis to monotypic species rank, and placed the remaining western and two eastern taxa as three subspecies of a second species P. leucogaster . Initial mtDNA analysis questioned both arrangements but could not include all taxa. We used mtDNA sequence data from all available specimens of the entire group (DNA extracted from cryo-preserved tissues, toe-pads and feathers; holotypes excepted) to derive a more stable view of species limits. The samples fell into two strongly divergent but geographically structured groups, completely reflecting the eastern and western components of the distribution. Thus we see merit in treating the two geographical groupings as two species, P. nigrogularis in the west and P. leucogaster in the east, each having two subspecies. Nuclear data could test whether the two western subspecies in particular are genetically isolated or currently exchanging genes.